Features of drawing therapy in the correction of anxiety in primary school children - Kozhurova, A.A.; Neustroeva, A.N. (EDP Sciences, 2021)
The article deals with the study of the nature of anxiety and its impact on personal development, manifested in primary school children. The aim of the study is to identify the features of the influence of drawing therapy on the correction of anxiety in primary school children. The hypothesis of the study is presented as an assumption that the correction of anxiety in children of primary school age will be more successful if a set of classes is used by the method of drawing therapy in compliance with the following pedagogical conditions: classes include various forms of drawing therapy for the correction of anxiety in children, including in remote mode in the conditions of quarantine measures of the pandemic; in the course of classes, adapted individual work is carried out. A description of the entire study on the tasks set is given: to identify the initial levels of anxiety in children; implement an empirical study on the adapted correctional program of drawing therapy and verify the results by monitoring the diagnosis of anxiety in primary school children. The research work is carried out on the basis of school No. 20. Yakutsk, among the students of the 4th grade in the number of 29 people.